1964
DOI: 10.1111/j.1365-2672.1964.tb04818.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Freezing on the Radiation Sensitivity of Vegetative Bacteria

Abstract: Summary: Five strains of bacteria were irradiated, suspended in heart infusion broth or in phosphate buffer, in aerated or anoxic conditions, at temperatures of 10–13° or ‐79°. Survivors under the different conditions were enumerated by plate counts on heart infusion agar. Exponential survivor‐dose curves were obtained with a Pseudomonas strain and with Escherichia coli B/r when irradiated at room temperature with aeration, whereas an Alcaligenes strain and 2 strains of Streptococcus faecium gave sigmoid curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…To determine whether the small amount of residual open circular DNA was the result of repair during irradiation (78 min on wet ice; -0°C), the cells were frozen on dry ice during irradiation (-70°C) and then rapidly melted and fixed by immersion in 100% ethanol. At the D37 under these frozen irradiation conditions (D37 = 3.0 megarads at -70°C; freezing of any bacteria, including D. radiodurans, increases radioresistance because of diminished DNA oxygen effects [26,31]), the extent of both chromosomal and plasmid breakage was identical to that seen at the D37 under the usual (-0°C) irradiation conditions (data not shown). Since no repair is likely to occur while the cells were frozen, we concluded that the presence of the same amount of residual open circular plasmid form seen following irradiation at -0°C is not the result of repair.…”
Section: Mater1als and Methodssupporting
confidence: 50%
“…To determine whether the small amount of residual open circular DNA was the result of repair during irradiation (78 min on wet ice; -0°C), the cells were frozen on dry ice during irradiation (-70°C) and then rapidly melted and fixed by immersion in 100% ethanol. At the D37 under these frozen irradiation conditions (D37 = 3.0 megarads at -70°C; freezing of any bacteria, including D. radiodurans, increases radioresistance because of diminished DNA oxygen effects [26,31]), the extent of both chromosomal and plasmid breakage was identical to that seen at the D37 under the usual (-0°C) irradiation conditions (data not shown). Since no repair is likely to occur while the cells were frozen, we concluded that the presence of the same amount of residual open circular plasmid form seen following irradiation at -0°C is not the result of repair.…”
Section: Mater1als and Methodssupporting
confidence: 50%
“…The D,, values for each organism are shown in The presence of oxygen might be expected to enhance the lethal effect of irradiaton, due to oxygen-radical formation. This phenomenon has been observed when organisms in buffer solutions were found to be more sensitive when irradiated under aerobic rather than anaerobic conditions (Matsuyama et al 1964). However, from the results obtained (Table 2) of D,, values in poultry mince, it is evident that atmosphere does influence the irradiation effect.…”
Section: Effect Of Atmosphere D U R I N G I R R a D I A T I O Nmentioning
confidence: 74%
“…Effect of frozen state on the radiation resistance of Y. enteroolitica. The radiation resistance of vegetative bacteria is usually two to five times greater in the frozen state than in the nonfrozen state (1, 4, 10,19,23 Effect of the suspending medium on the radiation resistance of Y. enterocolitica (strain IP107) at 25°C. A straight line was fitted as in Fig.…”
Section: Resultsmentioning
confidence: 99%